Genital endometriosis: pathogenesis, diagnosis, and association with malignancies - I.Yu. Ilina; D.V. Burdin; M.R. Narimanova; D.M. Ibragimova (LCC «Medicine-Inform», 2021)
I.Yu. Il'ina1, D.V. Burdin2, M.R. Narimanova1, D.M. Ibragimova1 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2N.I. Pirogov City Clinical Hospital No. 1, Moscow, Russian Federation Endometriosis is a hormone-dependent genetic disease that develops in impaired immune homeostasis. However, its pathogenesis remains an enigma. It is known that eutopic endometrium in women with endometriosis is different from that in healthy women. Morphologic examination of eutopic endometrium sample allows diagnosing endometriosis at an early stage. To date, the association between endometriosis and the risk of malignancies is in strong focus. Endometriosis is a benign disorder but shares similarities with malignancies, e.g., apoptosis resistance and stimulation of angiogenesis. Recent findings suggest that endometriosis is a precursor of clear cell and endometrioid ovarian cancer. Further studies are needed to identify novel markers of endometriosis for its timely diagnosis. Timely and adequate therapy reduces the prevalence of ovarian tumors. Further development of molecular studies on endometriosis and ovarian cancer predictors will uncover pathogenic mechanisms and find  potential preventive and treatment modalities. Keywords: endometriosis, ovarian cancer, eutopic endometrium, ectopic endometrium, apoptosis, angiogenesis. For citation: Il'ina I.Yu., Burdin D.V., Narimanova M.R., Ibragimova D.M. Genital endometriosis: pathogenesis, diagnosis, and association with malignancies. Russian Journal of Woman and Child Health. 2021;4(4):339-345 (in Russ.). DOI: 10.32364/2618-8430-2021-4-4-339-345.